A Pregnant Women’s Group: an Innovative Approach to Reduce Maternal and Neonatal Deaths in Developing Countries - Shrestha, Bhagawan Das (Journal of Advanced Academic Research, 2017)
In Nepal, the utilization of maternal, newborn and child health (MNCH) care services exhibit big gaps between rich and poor, for instance poorest quintile is at 10.7% skill births attendant services while richest at 81.5%, despite the services being free of cost. Pregnant women’s group (PWG) approach was initiated to address MNCH inequities prevailing in the disadvantaged community. The PWG is a socially cohesive peer support group of 8-15 pregnant women and postnatal mothers who meet monthly for participatory teaching and learning sessions on MNCH cares and semi-annual publicly group commitment meeting. At the meetings, husbands, mothers- in-law and father-in-law verbally commit to support their pregnant wives and daughters-in-law in present of pregnant women. Local health staff also commits to provide those services. The literature review was done on women’s group and its impact of MNCH. The findings were compared with PWG approach of Nepal in line with "the World Health Organization’s recommendation on community mobilization through facilitated participatory learning and action cycles with women’s groups for maternal and newborn health". The PWG approach fulfill the WHO’s consideration of more than 30% of pregnant women participation, the role of men and other members of the community, visual methods and ethnic group mix. The PWG approach can be a strategy to reduce the high burdens of maternal and newborn morbidity and mortality in developing countries. The approach needs monthly participatory teaching learning sessions, use of a behavioural mapping mat for self-monitoring and biannually publicly group commitments by husbands and mother and father-in-laws.Journal of Advanced Academic Research Vol. 3, No. 2, 2016, page: 66-81